Indonesian anti-inflammation herbs mechanism: mini review - Nuniek Nizmah. F Mochtar; Eko Mugiyanto; Wirasti wirasti; Vanesa Maharani; Novel Umarella; Hilda Fitria Wulandari; St. Rahmatullah; Widyastuti Handayani; Dwi Bagus Pambudi; Riska Kurnia Oktaviani; Achmad Vandian Nur; Yuliah Wahyu Permadi; Ainun Muthoharoh; Thanh-Hoa Vo; Muh. Nur Khoiru Wihadi (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
This mini-review aims to provide an overview of some commonly used anti-inflammatory herbs in Indonesia. Inflammation is a complex physiological response that plays a role in various diseases, and herbal remedies have been used traditionally in Indonesian culture for their potential anti-inflammatory properties. We utilize Portal Garuda as the primary database for searching herbs with anti-inflammatory activity using the keyword